Pendekatan Terapi Asthma-COPD Overlap (ACO): [The Approach of Asthma-COPD Overlap Syndrome Treatment] - Muhammad Amin; Alamsyah Sitepu (Jurnal Respirasi, 2017)
Asthma and COPD are the most common chronic airways disease and have different clinical manifestations and treatments. Asthma is an airway inflammatory disease mediated by Th2 cytokines, CD4 + lymphocytes and eosinophils, whereas inflammation of COPD is affected by Th1 cytokines, CD8 + lymphocytes and neutrophils. Asthma-COPD overlap (ACO) is the presence of persistent airflow limitations with some symptoms resembling asthma and some other symptoms similar to COPD. Current treatment of ACO is to target the dominant inflammatory phenotype of eosinophils and neutrophils. Treatments given to patients with dominant eosinophil phenotype are inhaled and anti-IgE corticosteroids, and the drugs under reasearch are anti-IL-5, anti-IL-13, GATA3 inhibitors, anti-IL-33, anti-IL-25 and anti-thymic stromal lymphopoietin (anti-TSLP). Treatment given to patients with dominant neutrophil phenotype was macrolide, and treatment under reasearch was anti-IL-1, anti-IL-17A, anti-IL-23, CXCR2 antagonists, p38 MAPK inhibitor / JAK inhibitors and PDE4 inhibitors. Paucygranulocyte patient were given LAMA, LAMA + LABA therapy and bronchial thermoplasty. The therapy currently under study for this group is triple inhalation.